2017
DOI: 10.1186/s13568-016-0308-7
|View full text |Cite
|
Sign up to set email alerts
|

Xylanases of Cellulomonas flavigena: expression, biochemical characterization, and biotechnological potential

Abstract: Four xylanases of Cellulomonas flavigena were cloned, expressed in Escherichia coli and purified. Three enzymes (CFXyl1, CFXyl2, and CFXyl4) were from the GH10 family, while CFXyl3 was from the GH11 family. The enzymes possessed moderate temperature stability and a neutral pH optimum. The enzymes were more stable at alkaline pH values. CFXyl1 and CFXyl2 hydrolyzed xylan to form xylobiose, xylotriose, xylohexaose, xylopentaose, and xylose, which is typical for GH10. CFXyl3 (GH11) and CFXyl4 (GH10) formed the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 31 publications
0
11
0
1
Order By: Relevance
“…Their (hemi)cellulolytic system was studied by growth in defined substrates, such as xylan or cellulose, revealing a complex array of enzymatic activities involved in polysaccharide utilization (Ponce-Noyola and De La Torre 2001;Amaya-Delgado et al 2006). Some individual GHs of both species have also been characterized, confirming their activity (Din et al 1990;Mayorga-Reyes et al 2002;Santiago-Hern andez et al 2007;Gao and Wakarchuk 2014;Lisov et al 2017;Yang et al 2015).…”
Section: Introductionmentioning
confidence: 90%
“…Their (hemi)cellulolytic system was studied by growth in defined substrates, such as xylan or cellulose, revealing a complex array of enzymatic activities involved in polysaccharide utilization (Ponce-Noyola and De La Torre 2001;Amaya-Delgado et al 2006). Some individual GHs of both species have also been characterized, confirming their activity (Din et al 1990;Mayorga-Reyes et al 2002;Santiago-Hern andez et al 2007;Gao and Wakarchuk 2014;Lisov et al 2017;Yang et al 2015).…”
Section: Introductionmentioning
confidence: 90%
“…4). Lisov et al (2017) found that the temperature optima for xylanases from Cellulomonas flavigena are 40 °C by CFXyl1 and 50 °C for CFXyl4, CFXyl3, and CFXyl2. Xylanases are stable below 60 °C and degrade rapidly at 65 to 70 °C (Amaya et al 2010).…”
Section: Enzyme Activity Assaysmentioning
confidence: 99%
“…The optimal pH of xylanase from C. flavigena was determined by Amaya et al (2010) to be 6.5 and 5.7 in C. fimi by Chen et al (2012). Xylanases show the highest stability at pH 8 to 10 (Lisov et al 2017). Table 1 shows the content of cellulose hemicelluloses and lignin content in the agricultural substrates.…”
Section: Enzyme Activity Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Diversos gêneros bacterianos já foram reportados como produtores de xilanases, como Bacillus, Cellulomonas, Micrococcus, Staphylococcus, Paenibacillus, Arthrobacter, Microbacterium, Pseudoxanthomonas eRhodothermus (Chakdar H et al, 2016). Algumas espécies, como Bacillusarseniciselenatis (Kamble RD, Jadhav AR, 2012), Cellulomonasflavigena (Lisov AV et al, 2017),…”
Section: Xilanasesunclassified